Study of Suspension Parameters Matching to Enhance Vehicle Ride Comfort on Bump Road - Jin Gao; Xiaoping Qi (Shock and Vibration)
In this study, the parameters of the MacPherson front suspension and the E-type multilink rear suspension are matched to enhance the vehicle ride comfort on bump road. Vehicle vibration and suspension stiffness are analyzed theoretically. In the simulation study, the influence of the front and rear wheels on the vehicle vibration is considered, so the time-domain curves of the front and rear seat rail accelerations are processed by adding windows with two different window functions. The resulting ΔRmsLocal and ΔRmsGlobal are used as evaluation indexes of the vehicle ride comfort. The sensitivity analysis yields the magnitude of the influence of the suspension parameters on the evaluation indexes. In addition, the trends of ΔRmsLocal and ΔRmsGlobal with bushing stiffness at different vehicle speeds are discussed. The results show that longitudinal ΔRmsLocal and ΔRmsGlobal of the seat rails are influenced by the bushings mostly, while the vertical ΔRmsLocal and ΔRmsGlobal of the seat rails are influenced by the spring and shock absorber mostly. The trends of ΔRmsLocal and ΔRmsGlobal with bushing stiffness are influenced by the speed of the vehicle. Finally, the vehicle ride comfort is enhanced after optimization and matching of the suspension parameters by NSGA-II optimization algorithm.